Keragaman Kualitas Fisik dan Kimia Buah Pepaya Calina di Balumbangjaya - Harliani Sri Utami; Susanto, Slamet; Dhika Prita Hapsari (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2022)
Papaya is a plant that can grow all year in Indonesia. Papaya has many varieties, so it has a variety of flavors, shapes, and sizes of the fruit. The diversity of superior papaya in the field should be evaluated to maintain its quality. The purpose of the research is to characterize and classify the diversity of physical and chemical qualities of Callina papaya. The sampling method used was the Purposive Random Sampling Method with a sample of 50 trees, each tree sampled four papaya fruits, so there were 200 total fruits. The sample tree is coded with a fruit shape based on the Descriptor for Papaya. The research was conducted from April to July 2022 at Papaya orchard in Babakan Lebak Village, Balumbang Jaya Village, West Bogor District, Bogor City, and the Post-Harvest Laboratory of the Faculty of Agriculture, IPB University. The results of the experiment showed that there were variations in the shape and cavity of the Callina papaya, namely elongate, lengthened-cylindrical, oval, and globular. Callina papaya has a fruit shape at the end of the stem of the depressed type and is classified as a small to medium-sized papaya fruit. The star-shaped papaya fruit cavity has a higher seed weight. The elongated and lengthened-cylindrical fruit has a shape in accordance with the description of the Callina papaya. Globular-shaped fruit has the higher TSS value as compared with other types. Fruit weight was positively correlated with length, diameter, flesh thickness.Keywords: tropical fruit, characterization, classification, fruit quality